Tensegrity Model Hypothesis: May This Paradigm Be Useful to Explain Hepatic and Pancreatic Carcinogenesis in Patients with Persistent Hepatitis B or Hepatitis C Virus Infection? - Fiorino, Sirio; Bacchi-Reggiani, Letizia; Pontoriero, Laura; Gallo, Claudio; Chili, Elisabetta; Masetti, Michele; Zanini, Nicola; Grondona, Ana; Silvestri, Tania; Deleonardi, Gaia; et al. (JOP. Journal of the Pancreas, 2014)
Context Hepatitis B (HBV) and hepatitis C virus (HCV) possess well-known oncogenic properties and may promote carcinogenesis in liver. However antigens and replicative sequences of HBV/HCV have been also detected in different extra-hepatic tissues, including the pancreas. Although epidemiological studies and meta-analyses have recently suggested that HBV/HCV may be also risk factors for pancreatic cancer and several researches have investigated the possible mechanisms and intra-/extra-cellular paths involved in pancreatic and hepatic carcinogenesis, to date, these complex processes remain largely unexplained. Objectives In our paper, we aimed to propose a comprehensive and qualitative hypothetical model, describing how HBV/HCV may exert their oncogenic role. Methods We performed a systematic research of scientific literature, by searching MEDLINE, the Cochrane Library and EMBASE databases. The used keywords were: “chronic HBV/HCV”, “pancreatic cancer”, “liver carcinoma”, “carcinogenesis mechanisms”, “tensional integrity”, “cytoskeleton”, and “extracellular matrix”. Results Taking advantage from available studies, we suggest an unifying hypothesis based on results and data, obtained from different areas of research. In particular we considered the well-defined model of tensional integrity and correlated it to changes induced by HBV/HCV in viscoelastic properties/stiffness of cellular/extracellular microenvironments. These events perturb the tightly-regulated feedback loop, which usually couples the intracellular-generated forces to substrate rigidity of extracellular compartments. Therefore, such a change strongly affects intracellular functions and cellular fate, by promoting a substantial deregulation of critical intracellular biochemical activities and genome expression. Conclusions Our hypothesis might provide for the first time a reliable system, which correlates tensional integrity model with intra-/extra-cellular modifications, occurring in liver and pancreas during HBV/HCV-induced carcinogenesis. This approach might improve our understanding of pathogenetic mechanisms involved in the development of pancreatic and hepatic carcinogenesis , enhancing the possibility of their treatment. Furthermore, should the usefulness of this model be definitively confirmed, it might be also helpful to extend its field of application to other viruses-related cancers. Image: Signaling pathways (Figure 1)